Tracing museum exhibition reviews: References, replies and translations between the museum space and the mass media. (April 2022) - Porsché, Yannik
Abstract: This paper traces how media dialogical networks are generated in interactions across different media. Reviews of a museum exhibition on public representations of immigrants in France and Germany serve as an example to follow connections between social interactions during guided tours in the exhibition space, comments written in the exhibition's guestbook and reviews of the exhibition published in newspapers. This contribution exemplifies how a contextualisation analysis allows us to disassemble how multiple voices and references are orchestrated in sequentially organised enunciations. The analysis shows, firstly, how journalists, museum staff, and visitors engage in face-to-face and written dialogues in which they refer to each other beyond co-present situations to politically position themselves, the museums and newspapers in relation to governmental politics; secondly, how members engage in disputes about networks' normative orders; and thirdly how multiple selection practices fundamentally change the meaning of enunciations in translations between modalities of the museum space and the mass media. Allegations of censorship give rise to professionals and laypeople in their reviews generating alliances and oppositions on the question how independent museums should be from the government.